(untitled) (American Journal of Arts and Human Science, 2024)
The aim of this study is to assess the status of Child rights in the two African countries of Sierra Leone and Lesotho. The study will begin by analysing the Treaties and conventions and bills, legal instruments relating to the protection of children signed by respective countries. The protection of children rights has increasingly become a significant focus for most countries in recent years, the evidence is that many countries of the world aim to protect children rights by Prioritising education, ending child marriages and child labour among others through the formulation of legislation and policies. Lesotho and Sierra Leone respectively have adopted and ratified various international bills and convections that aim to protect children’s rights. The paper will compare and analyse the strides and efforts of the two to protect children rights. Lastly, the paper will give out recommendations, strategies as well as lessons that can be adopted to further strengthen the protection of children rights in both countries.